Science of beauty face value - Crisp, Mary; Stone, Sharon; Hewes, Jonathan; Phillips, Katrina; Johnson, Fiona Scott; Cane, Georgann (Discovery Communications, 2007)
In this program, researchers are for the first time cracking the code of beauty using the science of evolutionary biology and psychology.